Noise in the ICU patient room – Staff knowledge and clinical improvements. (August 2016) - Johansson, Lotta; Knutsson, Susanne; Bergbom, Ingegerd; Lindahl, Berit
Summary: Introduction: The acoustic environment in the intensive care unit patient room, with high sound levels and unpredictable sounds, is known to be poor and stressful. Therefore, the present study had two aims: to investigate staff knowledge concerning noise in the intensive care unit and: to identify staff suggestions for improving the sound environment in the intensive care unit patient room. Method: A web-based knowledge questionnaire including 10 questions was distributed to 1047 staff members at nine intensive care unit. Moreover, 20 physicians, nurses and enrolled nurses were interviewed and asked to give suggestions for improvement. Results: None of the respondents answered the whole questionnaire correctly; mean value was four correct answers. In the interview part, three categories emerged: improving staff's own care actions and behaviour; improving strategies requiring staff interaction; and improving physical space and technical design. Conclusion: The results from the questionnaire showed that the staff had low theoretical knowledge concerning sound and noise in the intensive care unit. However, the staff suggested many improvement measures, but also described difficulties and barriers. The results from this study can be used in the design of future interventions to reduce noise in the intensive care unit as well as in other settings.